EVALUASI MANAJEMEN PENGELOLAAN OBAT DAN BAHAN MEDIS HABIS PAKAI (BMHP) DI DINAS KESEHATAN KABUPATEN AGAM TAHUN 2020 - Roza, Makhda; Elfindri, Elfindri; Almasdi, Almasdi (Universitas Gajah Putih, 2020)
Effective drug management and BMHP are needed to ensure the availability of drugs and BMHP in health facilities. The purpose of this study was to evaluate drug management and BMHP at the Agam District Health Office in 2020. This study uses qualitative methods, with in-depth interviews. Research informants amounted to 7 respondents. The research location is in the Health Office and 5 Community Health Centers in Agam Regency. The results of the study show that the management of drug management at the Agam District Health Office has not been maximized, including frequent delays in the delivery of Puskesmas plans and not according to needs. TPOT has not been effective, there are errors in recording stock cards, the number and types of drugs that are not according to the request of the Puskesmas, expired drugs and BMHP, lack of management staff, supervision and evaluation have not been effective, but procurement has been carried out according to applicable regulations. The conclusion of this study is that planning involves TPOT according to the planning stages. Submission of Puskesmas planning is still late and does not meet the needs. Procurement is carried out by the specified method. At the time of receipt, there are drugs that are close to expiry. Storage according to standards, but quality monitoring and maintenance of facilities are still lacking. There are drug vacancies and expired drugs. Distribution is done once in three months, there are quantities, types of drugs and BMHP that are not according to the request of the Puskesmas. Supervision and evaluation have not been effective. Disposal of drugs has not been carried out.